Adherence to nutrition‐based cancer prevention guidelines and breast, prostate and colorectal cancer risk in the MCC‐Spain case–control study. Issue 1 (21st April 2017) - Romaguera, Dora; Gracia‐Lavedan, Esther; Molinuevo, Amaia; de Batlle, Jordi; Mendez, Michelle; Moreno, Victor; Vidal, Carmen; Castelló, Adela; Pérez‐Gómez, Beatriz; Martín, Vicente; Molina, Antonio J.; Dávila‐Batista, Verónica; et al.
Abstract : Prostate, breast and colorectal cancer are the most common tumours in Spain. The aim of the present study was to evaluate the association between adherence to nutrition‐based guidelines for cancer prevention and prostate, breast and colorectal cancer, in the MCC‐Spain case–control study. A total of 1, 718 colorectal, 1, 343 breast and 864 prostate cancer cases and 3, 431 population‐based controls recruited between 2007 and 2012, were included in the present study. The World Cancer Research Fund/American Institute for Cancer Research (WCRC/AICR) score based on six recommendations for cancer prevention (on body fatness, physical activity, foods and drinks that promote weight gain, plant foods, animal foods and alcoholic drinks; score range 0–6) was constructed. We used unconditional logistic regression analysis adjusting for potential confounders. One‐point increment in the WCRF/AICR score was associated with 25% (95% CI 19–30%) lower risk of colorectal, and 15% (95% CI 7–22%) lower risk of breast cancer; no association with prostate cancer was detected, except for cases with a Gleason score ≥7 (poorly differentiated/undifferentiated tumours) (OR 0.87, 95% CI 0.76–0.99). These results add to the wealth of evidence indicating that a great proportion of common cancer cases could be avoided by adopting healthy lifestyle habits. Abstract : What's new? Prostate, breast and colon cancer share common environmental risk factors, but preventable causes remain largely unknown. Here the authors evaluated adherence to the World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) guidelines on diet, physical activity and body fat for cancer prevention and risk of these cancers in Spain. They found an inverse association between adherence to the recommendations and colon cancer, postmenopausal breast cancer and poorly differentiated prostate cancer, underscoring the important role of preventable causes in the development of these cancers.